Effectiveness of Mastery Learning Model Assisted by Table Tennis Ball Launcher in Improving Table Tennis Basic Skills Among Students - Sony Hasmarita; Yopi Meirijal; Akhmad Sobarna; Akhmad Dimyati; Joseph Lobo (Institute of Multidisciplinary Research and Community Service, 2026)
Table tennis is one of the compulsory sports in the Indonesian physical education curriculum, yet empirical evidence on effective instructional models for this discipline remains limited, particularly in the Cimahi region of West Java. Low student mastery of basic table tennis skills necessitates innovative pedagogical interventions to systematically improve outcomes. Objective: This study aimed to determine the effectiveness of the Mastery Learning model, assisted by a table tennis ball launcher, in improving students' basic table tennis skills, assessed against a minimum mastery criterion of 80 percent student completion. Methods: A one-group pretest-posttest design was employed with 50 students (30 male, 20 female) from SMP Negeri 3 Cimahi, West Java, Indonesia, selected through purposive sampling. The intervention consisted of eight weeks of Mastery Learning instruction, assisted by a table-tennis ball launcher (Newgy Robo-Pong). Pre-test and post-test data were collected using a standardized table tennis basic skills test (forehand, backhand, and service). Data were analyzed using a paired-samples t-test and N-Gain score analysis. Results: Post-test scores (M = 82.84, SD = 6.53) were significantly higher than pre-test scores (M = 63.22, SD = 9.12), t(49) = 13.84, p less than 0.001. The N-Gain score was 0.54 (in the moderate category). Forty-three of 50 students (86 percent) achieved mastery, exceeding the 80 percent criterion. Conclusion: The Mastery Learning model assisted by a table tennis ball launcher significantly improved students' basic table tennis skills and effectively met the minimum mastery standard. These findings suggest that technology-assisted mastery learning is a viable and effective approach for physical education in Indonesian schools.